Evaluating land use and emergency management plans for natural hazards as a function of good governance: A Case Study from New Zealand - Saunders W; Grace E; Beban J; Johnston DM (Beijing Normal University Press, 2015)
Plan evaluation is of utmost importance as a function of good governance. It provides a means to improve the institutional basis for implementing land use controls, provides an important opportunity to improve future plans to reduce risk, and improves the vision for sustainable development and management. This article provides an overview of the methods and findings of a plan evaluation project undertaken in New Zealand. The project analyzed 99 operative plans, provided in-depth analysis of ten plans, and included a capability and capacity study of councils. This is the first time all operative plans in New Zealand have had their natural hazard provisions assessed in this manner. The information provides an important baseline for future policy improvements, and a basis for future research and policy directions. The project found that, while New Zealand land use plans appear to be improving over time, there are still opportunities for improvement. These include improving linkages between objectives, policies, and rules within land use plans; and strengthening the linkages between land use and emergency management plans. The largest challenge is the accessibility, understanding of, and updating of hazard information.
Keywords: Emergency management plans; Land use plans; Natural hazards; New Zealand; Plan evaluation; 1801 Law